Smoking during pregnancy: a preventable silent epidemic in Colombia - Jorge E. Tolosa; Luis Guillermo Echavarría-Restrepo; Bernardo Agudelo J. (Federación Colombiana de Obstetricia y Ginecología, 2015)
The World Health Organziation (WHO) considers tobacco to be one of the main causes of preventable chronic disease and death around the world. Obstetric patients being exposed to tobacco products represents the most important preventable cause associated with intrauterine growth retardation (IUGR), preterm birth and low birthweight; it has also been associated with intrauterine fetal death and placental function-related abnormalities. In the neonatal period, it has been associated with sudden infant death syndrome, infections, such as otitis and pneumonia, and in infancy with chronic diseases, such as asthma and obesity.1,2 Tobacco consumption affects all age-groups; however, there has been a worrying increase in susceptible populations (i.e. adolescents and young people). Girls and women currently represent specific targets for the tobacco industry involving the indiscriminate promotion of tobacco and cigarette consumption.3 Global surveys have revealed a disturbing increase in cigarette and tobacco use in girls aged 13-15; however, such increase in consumption has not affected all countries in the same way. High-income countries (according to World Bank classification of countries by income) have seen a reduction in tobacco use whilst consumption has increased in countries classified as being low or medium/high income ones, such as Colombia.3 It has been calculated that 9% of females smoke in low-income countries. young females are becoming increasingly exposed to this scourge and one out of four adolescents currently becomes pregnant in Colombia. (http://www.who.int/tobacco/resources/publications/toacco_atlas/en/index.html).